SEGMENTASI PASAR JASA REKREASI RUTAN - Satria Astana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1998)
The significant implication of research on further development of forest recreation service depends on the progress of market research on the service itself. As a part of the effort to addressing such issue, this study aims at identifying the market segments of recreation service at three sample forest units, namely: Carita, Situgunung and Sukamantri, all in West Java. The study reveals that university students, private officers and high school students, mostly living in Jakarta, were respectively significant variables for segmenting markets of the service offered. In addition, the marketing management of the service has been ineffectively designed, targeted and promoted to other growing markets such as young families with middle income status.